Visual Occipito-Temporal N1 Sensitivity to Digits Across Elementary School - Fraga-González, Gorka; Di Pietro, Sarah V.; Pleisch, Georgette; Walitza, Susanne; Brandeis, Daniel; Karipidis, Iliana I.; Brem, Silvia (Frontiers in Human Neuroscience, 2022)
Number processing abilities are important for academic and personal development. The course of initial specialization of ventral occipito-temporal cortex (vOTC) for visual number processing is crucial for the development of numeric and arithmetic skills. We examined the visual N1, the electrophysiological correlate of vOTC activations across five time points in kindergarten (T1, mean age 6.60 years), middle and end of first grade (T2, 7.38 years; T3, 7.68 years), second (T4, 8.28 years) and fifth grade (T5, 11.40 years). A combination of cross-sectional and longitudinal EEG data of a total of 62 children (35 female) with varying familial risk for dyslexia were available to form groups of 23, 22, 27, 27 and 42, participants for each of the five time points. The children performed a target detection task which included visual presentation of single digits (DIG), false fonts (FF), and letters (LET) to derive measures for coarse (DIG vs FF) and fine (DIG vs LET) digit sensitive processing across development. Our N1 amplitude analyses indicated coarse and fine sensitivity across time points as shown by a stronger N1 to digits than false fonts across all five and stronger N1 to digits than letters in four out of five time points. In addition, arithmetic skills were negatively associated with coarse N1 digit sensitivity over the left hemisphere at T4, possibly reflecting allocation of more attentional resources or stronger reliance on the verbal system in children with poorer arithmetic skills. To summarize, our results show persistent visual N1 sensitivity to digits that is already present early on in pre-school and remains stable until fifth grade. This pattern of digit sensitivity development clearly differs from the relatively sharp rise and fall of the visual N1 sensitivity to words or letters between kindergarten and middle of elementary school and suggests different trajectories in the development of visual processing for written characters that are relevant to numeracy and literacy.